Parents and teachers - edited by Timothy V. Rasinski (Harcourt Brace College Publishers, 1995)
This textbook educates teachers and parents about the potential they have, when they work together, to improve children's literacy development. The book provides teachers with sound information that they can communicate to parents about literacy education that can be developed at home and in the schools